The Occurrence of Heavy Metals Accumulation in the Organs and Tissues of Clarias gariepinus from River Hadejia and Nguru Lake - Musa Mohammed, Ibrahim; Maizare, M. U.; Wakil, M.; Zannah, U. B.; Abdullateef, M. M. (Sahel Journal of Life Sciences FUDMA, 2025)
Contamination by heavy metals in fish is of significant interest. The occurrence of Heavy metals in fish is an important issue because fish are consumed as a source of protein and, when consumed, could cause serious harm to human health. The study aims to assess levels of heavy metals in different tissues of Clarias gariepinus obtained from the River Hadejia and Nguru Lake. The gills, liver, and muscle were dissected and analyzed for the presence of lead, cadmium, and chromium using the atomic absorption spectrophotometer. Also, oxidative enzymes were measured in the tissues of the fish using standard protocols, and histological examination was carried out to reveal alterations in tissues. Results revealed high heavy metal content in fish, for instance, fish from Hadejia River had a Pb concentration of 29.97mg/Kg, 17.53mg/Kg, and 20.93mg/Kg in the gills, liver, and muscles respectively, as Cd concentration of 2.41mg/Kg, 2.17mg/Kg and 5.43mg/Kg was observed in the gills, liver, and Muscle of fish from Nguru Lake. Antioxidant enzyme activities showed that superoxide dismutase (SOD), glutathione (GSH), and catalase (CAT) were all at elevated levels in the fish. Histology examination showed varying degrees of alterations with the gill filaments showing proliferation of cells, clubbing, lamella cell hyperplasia, and fusion in the fish at both water bodies, indicating high levels of toxicity in the fish. These results reveal contamination and a corresponding effect in antioxidant production as an adaptive response to oxidative damage, highlighting serious consequences in the consumption of fish obtained from both water bodies.